2005
DOI: 10.1038/sj.tpj.6500352
|View full text |Cite
|
Sign up to set email alerts
|

(AAT)n repeat in the cannabinoid receptor gene (CNR1): association with cocaine addiction in an African-Caribbean population

Abstract: Owing to their agonist action on dopaminergic systems, cannabinoids may play a major role in substance dependency and schizophrenia. We examined the (AAT)n triplet repeat polymorphism nearby the CNR1 gene, which encodes human cannabinoid (CB1) receptor, in a male Afro-Caribbean population. The allelic and genotypic distributions were significantly different in non-schizophrenic cocaine dependents (n ¼ 97), schizophrenic cocaine dependents (n ¼ 45) and matched controls (n ¼ 88) (Po10 À4 ). The frequency of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
55
0
3

Year Published

2006
2006
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(62 citation statements)
references
References 21 publications
4
55
0
3
Order By: Relevance
“…Rimonabant, the CB 1 R antagonist, has shown some efficacy in clinical trials for nicotine cessation. 159 Several studies have also found associations of (AAT) n 12-repeat polymorphisms near CNR1, encoding the CB 1 receptor, with increased cocaine dependency 160 but smoking has not been studied directly. A 365 C4A SNP in the gene encoding fatty acid amide hydrolase, the main degradative enzyme for endocannabinoids, decreases enzyme expression and activity.…”
Section: Other Likely Candidates Involved In Neurotransmitter Systemsmentioning
confidence: 99%
“…Rimonabant, the CB 1 R antagonist, has shown some efficacy in clinical trials for nicotine cessation. 159 Several studies have also found associations of (AAT) n 12-repeat polymorphisms near CNR1, encoding the CB 1 receptor, with increased cocaine dependency 160 but smoking has not been studied directly. A 365 C4A SNP in the gene encoding fatty acid amide hydrolase, the main degradative enzyme for endocannabinoids, decreases enzyme expression and activity.…”
Section: Other Likely Candidates Involved In Neurotransmitter Systemsmentioning
confidence: 99%
“…The 1359A/G polymorphism (rs1049353) in the coding exon of CNR1 (exon 4) has also been associated with vulnerability to alcohol withdrawal delirium (Schmidt et al, 2002). Additionally, the rs806380 SNP located in intron 2 of the CNR1 gene was significantly associated with developing one or more cannabis dependence symptoms (Hopfer et al, 2006), and the (AAT)n triplet repeat polymorphism nearby the CNR1 gene was found to be associated with cocaine addiction in an African-Caribbean population (Ballon et al, 2006). However, several studies have also failed to find association of the CNR1 receptor polymorphism and substance dependence phenotypes (Herman et al, 2006;Li et al, 2000;Preuss et al, 2003).…”
mentioning
confidence: 99%
“…Furthermore, prior use of cannabis was found to enhance the "high" elicited by subsequent use of cocaine in humans (Foltin et al, 1993;Lukas et al, 1994) and also to hasten relapse in abstinent former cocaine users (Rawson et al, 1986). Furthermore, a recent genetic study found an association between an (AAT)n triplet repeat polymorphism in the CNR1 gene encoding the CB 1 receptor with cocaine addiction in an African-Caribbean population (Ballon et al, 2006). Treatment with HU-210 promoted reinstatement of cocaine-seeking behavior in rats, whereas treatment with SR141716 prevented reinstatement (De Vries et al, 2001).…”
mentioning
confidence: 99%